DILEMATIKA FATWA DSN-MUI DAN FATWA TUAN GURU TENTANG HUKUM EKONOMI SYARIAH DI KECAMATAN GUNUNGSARI LOMBOK BARAT - S, MUZAKKIR. (Alif Lam : Journal of Islamic Studies and Humanities, 2025)
The dilemma of applying DSN-MUI fatwa with the fatwa of teachers in the community on the application of sharia economic law is caused by many factors. This study uses a qualitative approach with socio-legal study methods to analyze the dilemmas of DSN-MUI fatwa and Tuan Guru's fatwa in sharia economic law. The implementation of the DSN-MUI fatwa received rivalry from local religious leaders not to look for weaknesses but to find common ground between the two. At the local level, the authority of Tuan Guru has great influence in determining the legal practice of sharia economics. The difference in interpretation between the DSN-MUI fatwa and the Tuan Guru fatwa often raises dilemmas, especially in the practice of people's economic life. The dilemmatic fatwa is a challenge for the existence of DSN-MUI fatwa because the legal determination taken by the teacher is considered more authoritative and based on strict prudence.